Analysis of The Effects of Size Population, Unemployment, and Government Expenditures on Poverty Levels in Mimika Regency 2011-2023 - Stenlly Befry Tutkey; Ivan Rahmad Santoso; Fitri Hadi Yulia Akib (Universitas Nusantara PGRI Kediri, 2025)
This research aims to determine the influence of size population, unemployment, and government expenditures on poverty levels in Mimika Regency in 2011-2023. The data used in this research uses secondary data sourced from the Mimika Regency Central Statistics Agency and the Directorate General of Financial Balance, Ministry of Finance. This research uses a multiple linear regression analysis method using the OLS (Ordinary Least Square) model. Data processing uses Eviews 10 statistical testing. The results of this study show that size population has a partial positive and insignificant effect on poverty levels. Unemployment has a positive and insignificant effect on poverty levels, and government expenditures have a negative effect on poverty levels. The results of simultaneous statistical tests show that population, unemployment, and government expenditures did not have a significant effect on poverty level in Mimika Regency in 2011-2023.